Systematic measurement error in self-reported health: Is anchoring vignettes the way out? - Aparajita Dasgupta (IZA Journal of Development and Migration, 2018)
This paper studies systematic reporting heterogeneity in self-assessed health in India using World Health Survey (WHS)-SAGE survey that has subjective assessments on own health and hypothetical vignettes as well as objective measures like measured anthropometrics and performance tests on a range of health domains. The study implicitly tests and validates the assumption of response consistency in a developing country setting, thus lending support to the use of vignettes. Additionally, we are able to control for unobservable heterogeneities of reporting behavior at the individual level by employing individual fixed-effects estimation using multiple ratings on a set of vignettes by the same person. The study confirms identical pattern of systematic bias by the socioeconomic subgroups as is indicated by vignette technique. It further highlights that substantial amount of reporting heterogeneity remains unexplained after controlling for the usual socioeconomic control variables. The finding has potentially broader implications for research based on self-reported data in a developing country.
Keywords: C83; D91; I12; I18; I15; I32; J10; 330; Self-assessed health; Vignette approach; Measurement error; Response consistency